Development of EST-SSR Markers to Assess Genetic Diversity in Elettaria Cardamomum Maton - Anjali, N; Dharan, Sowmya S; Nadiya, F; Sabu, K K (International Journal of Applied Sciences and Biotechnology, 2015)
Elettaria cardamomum Maton is one of the most ancient and valuable spice crops. Cardamom is cultivated following intensive pesticide usage where alleles present in the wild cardamom genotypes could positively contribute towards genetic improvement of the cultivars. However, the genetic map or whole-genome sequence of E. cardamomum is not available and very limited information on simple sequence repeat (SSR) markers are publicly available. We have tested whether SSRs from Curcuma longa can be used to analyze genetic diversity E. cardamomum. Int J Appl Sci Biotechnol, Vol 3(2): 188-192 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12380